2022
DOI: 10.3390/ijms23063091
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Urease: Potential Contributions to Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) causes dementia and memory loss in the elderly. Deposits of beta-amyloid peptide and hyperphosphorylated tau protein are present in a brain with AD. A filtrate of Helicobacter pylori’s culture was previously found to induce hyperphosphorylation of tau in vivo, suggesting that bacterial exotoxins could permeate the blood–brain barrier and directly induce tau’s phosphorylation. H. pylori, which infects ~60% of the world population and causes gastritis and gastric cancer, produces a pro-i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 91 publications
1
13
0
Order By: Relevance
“…A previous study also showed indirect neuroinflammation in microglia via HP-stimulated stomach, elevating iNOS and NO [81]. Additionally, HPurease-stimulated microglia showed elevated ROS and cytokines such as IL-1β and TNF-α [82]. Building on prior limitations, our study validated central innate immunity responses, including microglia and astrocytes, upon HPCFS stimulation.…”
Section: Discussionsupporting
confidence: 71%
“…A previous study also showed indirect neuroinflammation in microglia via HP-stimulated stomach, elevating iNOS and NO [81]. Additionally, HPurease-stimulated microglia showed elevated ROS and cytokines such as IL-1β and TNF-α [82]. Building on prior limitations, our study validated central innate immunity responses, including microglia and astrocytes, upon HPCFS stimulation.…”
Section: Discussionsupporting
confidence: 71%
“…These studies suggest that probiotics can directly act on GSK-3β pathway and alleviate tau hyperphosphorylation. Furthermore, probiotic has been proven effective in treating gastric infection caused by H. Pylori ( Aiba et al, 2015 ), which induces tau hyperphosphorylation in mouse hippocampal tissue ( Wang et al, 2014 ; Uberti et al, 2022 ), via the GSK-3β pathway ( Wang et al, 2014 ). Dysregulation of gut microbiota via gut-brain axis is associated with AD and probiotic supplement has the potential of correcting tau hyperphosphorylation through GSK-3β suppression.…”
Section: Probiotic Therapy Reducing Tau Hyperphosphorylation ...mentioning
confidence: 99%
“…It was demonstrated that the pro-inflammatory properties of urease promote the transformation of endothelial cells into reactive oxygen species (ROS)-dependent differentiation programs that contribute to H. pylori infection ( de Jesus Souza et al., 2019 ). In addition to its strong association with various diseases, such as gastritis and peptic ulcer, previous research has established a link between the H. pylori urease and extragastric diseases, such as AD, which relates to the pro-inflammatory activity of urease and activation of the immune system, causing neuroinflammation and tau phosphorylation ( Uberti et al., 2022 ). Using urease inhibitors to suppress urease function is, therefore, a potentially promising strategy for eliminating H. pylori .…”
Section: Pathogenesismentioning
confidence: 99%